A Tale of Two Hates: Testing of the Duplex Theory - Al-Badayneh, Diab M.; Alkubaisi, Hussen Thani (Journal of Cultural Analysis and Social Change, 2026)
This research study focuses on a central premise of Sternberg's (2003) Duplex Theory of Hate. It explored the relevance of attitudes, exposure to hate speech, and behavior as mediators through a model of the Duplex Theory of Hate. Recent findings from a regression analysis of 141 participants highlight the relationship between such factors and hate sentiments. The results indicated significant interrelationships between emotional constructs, particularly regarding the Negative Intimacy (NI) differentiators, Hate Theory Scale (HTS), and Decision & Commitment (D&C), each showing a high correlation coefficient of r = .88. This indicates that those who are experiencing strong negative intimacy have more investment in feelings of hate. Moreover, the different criteria variables of hate (CVH) were moderately positively related with HTS (r = .53) and D&C (r = .46), which suggests that negative criteria can magnify hate sentiments. Correlation of HTS with Attitudes (A = r = .57) and CVH (r = .78), identifying negative attitudes as underlying factors of hate dynamics. In contrast, Behavior (B) exhibits lower correlations, especially with Exposure to Hate (EH) (r = .58) and CVH (r = .86), indicating that while hate may stem from emotions and attitudes, behavioral responses may be influenced by something else. Finally, EH is associated with D&C (r = .41) and CVH (r = .81), and they argue that exposure is a critical influence for attitudes towards hate. The regression model is statistically significant (p < 0.001), indicating that at least one of the predictor variables explains hate's variance in the scale severity measure. Attitudes, exposure, and behavior explained 39% of the variance, with a moderate to strong relationship between these (R = .62). Attitudes also appeared as a significant positive predictor (coefficient of 1.703, p < .001), highlighting the importance of addressing attitudes in hate reduction approaches. Likewise, exposure to hate speech was also positively associated (B = 1.279, p < .001), indicating that interaction with differing viewpoints can curtail polarized attitudes. However, behavior did not reach statistical significance and may need to be re-evaluated. The research emphasizes that attitudes (and their countering) and exposure to hate speech are important, and—according to the authors—future studies should include demographic details of respondents and socio-economic factors in order for effective interventions that foster social cohesion by decreasing hate to be developed.